Pandorina morum genome assembly, annotation, and analysis - Heffel, Matthew George (Kansas State University, 2020)
The evolution of multicellularity is a major evolutionary transition that leads to increased organismal complexity and has occurred various times in multiple domains of life. Despite its common occurrence, the evolution of multicellularity is not yet well understood largely due to genetic signatures being lost due to deep divergence between unicellular and multicellular lineages. The volvocine algae have recently made the transition to multicellularity (200 MYA) and cover a large range of morphologies, including unicellular Chlamydomonas, undifferentiated multicellular Gonium (8-16 cells), multicellular isogamous Pandorina (8-16 cells), multicellular isogamous Yamagishiella (32 cells), multicellular anisogamous Eudorina (32 cells), and multicellular differentiated Volvox with germ-soma division of labor (>500 cells). Using modern sequencing techniques, here, the genome of Pandorina morum is sequenced, assembled, and annotated. Brief comparative genomics work shows gene orthology to related volvocine species as well as a common trend of progressive gene loss occurring at a higher rate than gene gain and organismal complexity increases. This work opens the door to targeted mutagenesis as transgenic work using both foreign genes in Pandorina and genes from Pandorina in related species.
Keywords: Pandorina Genome Assembly; Transcriptome; Multicellularity; Genomics